Pengembangan Kriteria Status Mutu Ekosistem Danau Sebagai Bagian Dari Indikator Pengelolaan Terpadu Wilayah Sungai - Irianto, Eko Winar; Triweko, Robertus Wahyudi; Yudianto, Doddi (JURNAL TEKNIK HIDRAULIK, 2010)
High rate of pollution on the watershed has impacted to deteriorate water quality reservoirs. Officially, Quality Status of Reservoir Ecosystem has not been established yet. So, this study describes the accomplishment of integrated watershed management using Quality Status of Lake Ecosystem criteria (SMED) formulated by ministry of environment. The application of the criteria to Saguling and Sutami reservoirs datas shows that quality status of the reservoir ecosystems are in threat conditions. In order to apply the SMED criteria for assessment of quality ecosystem in reservoir, the advance experiments are still needed mainly for the additional indicators as following: 1) integration bluealgae and biodiversity indicator with biodiversity index; 2) suitability of land erosion indicator connected with reservoir design of erosion rate; 3) shifting of siltation lake indicator siltation reservoir indicator in relation with the percentage of dead storage volume; 4) integration hydroelectric power and water resources exploitation associated with the hidrological reservoir and water balance; 5) suitability of fish cage calculation in reservoir, 6) suitability of water quality indicator related with water quality standard; 7) addition of corrosivity index and quality of bottom sediment in reservoir. To facilitate apply the SMED for the assessment of reservoir ecosystem.